Uçuş Notları - Güray, Semih (Aviation, 2021)
What's happening with airplanes? What's going on in the air? These questions always occupy our minds, and we always wonder about their answers. In this book, you will find answers to your questions about the aviation sector and aircraft in general. You will also find important or interesting events that have been recorded as milestones in aviation history. Through this study, prepared as a bedside book for those with an interest in aviation and those who are curious about what's going on in the air, you will find different information and answers to many of the questions you may have.